Implementasi Manajemen Kelas di SD Negeri Yamo Puncak Jaya Papua Tengah - Tabuni, Dion; Andayani, Endah; Sari, Yuli Ifana (Jurnal Penelitian dan Pendidikan IPS, 2024)
This study aims to find out the overview of the implementation of classroom management in SD Negeri Yamo Puncak Jaya and to find out whether there are supporting and inhibiting factors in the implementation of classroom management at SD Negeri Yamo Puncak Jaya. The research method used is a qualitative method with a descriptive type. The subjects of the study include: the principal and teachers of SD Negeri Yamo Puncak Jaya. Data collection techniques include observation, interview, and documentation techniques. Data analysis techniques include: data collection, data reduction, and conclusion drawn. The validity of the data in this study uses triangulation. The results of the study show that the implementation of classroom management in improving the quality of learning at SD Negeri Yamo is very significant. This can be said to be significant when implementing physical management and student management. A conducive and minimum physical environment supports the increase in the intensity of the learning process and has a positive influence on the achievement of learning objectives. And the supporting factor in classroom management at SD Negeri Yamo is the physical condition of the classroom or adequate classroom building and facilities because the physical environment of the learning place has a very important influence on learning outcomes and has a positive influence on the achievement of learning goals. The inhibiting factor in the implementation of classroom management at SD Negeri Yamo is the family factor because the behavior of students in the classroom is a reflection of their family situation.